How do Indonesian EFL students writing strategies and writing process differ from English L1 students? - Fajrina, Dian; Everatt, John; Fletcher, Jo; Astall, Chris; Sadeghi, Amir (Universitas Syiah Kuala, 2023)
This research aimed to investigate the writing strategies applied by English as a Foreign Language (EFL) students in Indonesia. It also investigated how the writing process undergone by Indonesian EFL students differs from students using English as their first language (L1). The writing strategies questionnaire from Petri and Czrl (2003) was used to find out the strategies used by the EFL students. In addition, the adult writing process model of Hayes (2012), which was constructed based on the writing process of English as first language students, was used as the framework to investigate the writing process applied by Indonesian students. The participants were 135 English Education department students from two Indonesian universities. Participants answers to the questions in the questionnaire over the three stages of writing (pre-writing, drafting, and revising) were analysed using a 5-point Likert scale. The result revealed that the participants applied writing strategies at a moderate level. They only frequently used 15 of the 38 strategies provided in the questionnaire at high frequency. The 15 strategies used at high frequencies described the participants writing process which indicated some differences from that of the writing process undergone by the English L1 students. The findings aim to inform theories of second/foreign language writing performance, as well as support the design of teaching writing courses in English Education majors in Indonesia. The data may also be useful for educators in other countries teaching English as a second or foreign language.